Bilateral incidental benign Brenner’s tumors with unilateral mucinous cystadenoma of ovary – a rare case report - Raut, Sonal T.; T. P., Meera (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Brenner tumors are unilateral and in 5-7% of cases the tumors are bilateral. These tumors are usually identified incidentally during imaging studies or surgery in post-menopausal women. Histologically, BTs are characterized by well-circumscribed nests of transitional epithelium surrounded by a fibromatous background. Brenner tumors are known to coexist with mucinous tumors of ovary. We have presented a rare case in 43-year-old pre-menopausal women presented with heavy bleeding reported as bilateral incidental Brenner’s tumor associated with unilateral mucinous cystadenoma along with other pathologies like benign endometrial polyp, adenomyoma and paratubal cyst. It highlights the awareness for extensive sampling of bilateral ovaries because of the common association with mucinous cystadenomas.